Genome-wide identification and tissue-specific expression analysis of nucleotide binding site-leucine rich repeat gene family in Cicer arietinum (kabuli chickpea) - Sharma, R.; ,Rawat, V.; Suresh, C.G. (Genomics Data, 2017)
The nucleotide binding site-leucine rich repeat (NBS-LRR) proteins play an important role in the defense mechanisms against pathogens. Using bioinformatics approach, we identified and annotated 104 NBS-LRR genes in chickpea. Phylogenetic analysis points to their diversification into two families namely TIR-NBS-LRR and non-TIR-NBS-LRR. Gene architecture revealed intron gain/loss events in this resistance gene family during their independent evolution into two families. Comparative genomics analysis elucidated its evolutionary relationship with other fabaceae species. Around 50% NBS-LRRs reside in macro-syntenic blocks underlining positional conservation along with sequence conservation of NBS-LRR genes in chickpea. Transcriptome sequencing data provided evidence for their transcription and tissue-specific expression. Four cis-regulatory elements namely WBOX, DRE, CBF, and GCC boxes, that commonly occur in resistance genes, were present in the promoter regions of these genes. Further, the findings will provide a strong background to use candidate disease resistance NBS-encoding genes and identify their specific roles in chickpea.